Self and counterfeit consumption in emerging markets - Moutusi Tanha; Akib Mahumd; Mahfuza Sultana; Tozim Chakma; Emam Mehede Hassan; Sajid A. Mabud; Md. Ferdous Rahman Razon; Sheikh Shahanewaz parvez; Azmol Hossain Joy (goodwood publishing, 2022)
Purpose: This research has focused on independent and interdependent self-concepts of fake self & pretentious consumption in counterfeit consumption. In this research role of self in the case of fake consumption in the emerging market of Bangladesh has been revealed Research methodology: For this study, qualitative research has been undertaken. Ethnographic and netnographic approaches have been used. Twenty in-depth interviews were conducted with the participants. The participants were approximately equal as far as gender was concerned. The participants were between 20-35 years old; 80% were students, and 20% were employed. The snowball sampling technique was used for sample selection. Participants were selected for the final interview after the initial screening to know the pattern of their behavior, preferences, and experience with counterfeit & luxury brands. The Facebook profiles of these participants were studied to find photos, posts, shares, and preferences for counterfeit and luxury brands. Results: The results reveal that consumers feel their missing self, which means they understand they don't have appropriate possessions, and the extended self means a self that is created by external objects, some particular possessions considered as a part of them. As a result, they try to show their imaginary self, which means they try to copy others, but when they fail, they start to show their fake self through counterfeit consumption. Limitations: The research is conducted within Bangladesh only. Contribution: This research has focused on the patrons of the emerging market of Bangladesh. Findings have been revealed through a projective technique using word and picture associations. The iterative hermeneutic method has been used for data analysis. The research results conclude that variation in self affects the inauthentic consumption behaviors of patrons in the emerging market of Bangladesh.